Retrogradation Properties of Heat Moisture Treated (HMT) Sago and Arenga Starches - Dede Robiatul Adawiyah; Tomoko Sasaki; Kaoru Kohyama (Indonesian Food and Nutrition Progress, 2020)
This study aimed to investigate the retrogradation rate of heat moisture treated sago and arenga starches using different approaches, including a thermal approach using DSC (differential scanning calorimetry), a rheological approach using dynamic viscoelasticity as rheological and syneresis level. The autoclaving procedures prepared the HMT starches at 20% moisture content and warmed to 120 °C for 60 min and 90 min for sago and arenga starches, respectively. The Avrami equation was used to express starch retrogradation kinetics based on gelatinization enthalpy (ΔH). The Avrami exponent (n) of HMT and native starches were close to 1.0 (0.77 – 1.20) indicates rapid nuclei growth of the crystal. HMT has a significant influence on the retrogradation of sago starch, both from the values of n and k of the Avrami equation. On the other hand, it does not have a significant effect on arenga starch. Based on the thermal approach (DSC), HMT significantly affects sago starch’s retrogradation rate, but there was no effect on arenga starch. The influence of HMT on the retrogradation rate of arenga starch was observed on rheology and syneresis approaches, although it was not as high as sago starch.